New in US-Canadian Relations and Ratification of the USMCA Agreement - I. A. Sokov (Vestnik MGIMO-Universiteta)
Abstract: The article reviews through chronological analysis key issues in US-Canadian relations in the context of new trade agreement USMCA replacing NAFTA during Trump's presidency. It identifies a new model of relations between the closest North American partners in the context of a new paradigm which is called “America First”. This model leads to a crisis the US-Canadian relations, which is aggravated by the increased partisan rivalry in light of the upcoming US presidential elections, the impeachment process initiated in the House of Representatives.The article comes to the following conclusions. The evolutionary development of the free trade agreement (NAFTA), its rejection and acceptance of the USMCA preferential agreement is a gradual and consistent process of protecting North American countries from global market, which started during the presidency of George W. Bush and continued by the subsequent American presidents. This is also connected with the trade war between the United States and China, that was repeatedly emphasized both in the US Administration and in the Congress during D. Trump's presidency. The United States-Canadian relations have worsened significantly, although the countries' leaders do not recognize it publicly during the agreement's preparation and its ratification, for almost three years. The USMCA agreement is not a final version, subject to further ratification. It took more than a year for the parties to find compromise solutions on the USMCA with the protocols' preparation to the agreement and its submission to the national parliaments. Moreover, in the agreed version, the USMCA agreement meets primarily the interests of the United States. The US pressure on Canada was unprecedented. As a result, we should expect the continued growth of political and trade contradictions between the United States and Canada, as well as the revision and addition of new additional agreements in the USMCA agreement.